The Treatment of Nonperforming Loans in Macroeconomic Statistics - Gorter, Cornelis (IMF Working Papers; Working Paper, 2001)
This paper seeks to promote discussion on the treatment of nonperforming loans in macroeconomic statistics. After reviewing current recommendations in international statistical manuals and the guidelines provided by some main banking and accounting institutions, the paper recommends that the information on nonperforming loans provided by macroeconomic statistics should be expanded. The paper concludes with a list of issues that deserve further study.